Visual vertigo: Vertigo of oculomotor origin. (July 2018) - Chin, Seong
Abstract: Since Róbert Bárány proposed his hypothesis on vestibulo-ocular reflex (VOR), dizziness associated with vertigo has been interpreted as being vestibular in origin. However, there have been many contradictory findings showing modulations of VOR, which have caused confusion as to VOR's role and accuracy. Further, there seems to be an influence of VOR when the anatomical inner ear structures are congenitally absent. Many people report vertiginous symptoms when they are exposed to visually challenging situations. These people with visually induced vertigo are usually found to have only mildly abnormal labyrinthine findings. Accurate visual information via binocular vision in animals, including humans, is important for the survival. Understanding how visual information is used in balance can help us to apply a different approach to the mechanism of vertigo. This article will review how accurate binocular viewing is possible for precise images through a complex oculomotor system and the proprioceptive senses of the external ocular muscles (EOMs). The proprioceptive senses from EOMs appear to affect motor efferents of the body. Oculomotor activities during viewing are important not just for learning but also for executing whole body motor responses. An error in the oculomotor afferents will cause a reaction to the error signal. This can be troubling for proper balancing during movement. Especially, common oculomotor causes (including fatigue of EOMs which is common in today's lifestyle) can contribute to many vertiginous conditions.